Former les cadres d’établissements scolaires - Frédéric Yvon; Jean-Marc Huguenin (Éducation et Socialisation)
This text focuses with the possibility of training school principals based on their real activity. First, it examines the potential of using data on principals’ shadowing. Second, having experienced the limits of this approach, the text considers the paradox approach to put into perspective the dilemmas and hesitations experienced by school principals in their functions of management. Finally, it introduces a training program that aims to identify, understand, and discuss these paradoxes, and in particular ways of managing and coping with them.